Harmonizing Nature and Knowledge: Crafting Engaging Thematic Teaching Tools for Expedition on Environmental Preservation - Herawati, Helma; Khairinal, Khairinal; Idrus, Ali (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2023)
The purpose of this research consists of : 1) presenting about teaching materials compiled in detail in accordance with the environmental theme which will be presented, in the thematic teaching process in the first semester for third grade of elementary school; 2) produce a thematic textbook in the first semester for third grade of elementary school with the environmental theme which used by teachers and students. Method  of this research is research and development. The sample used in this research was grade 3 elementary school students. The analysis technique used was qualitative data in the form of responses, consultation results and suggestions for improvements from design experts and material experts. The novelty of this research is that this innovative study pioneered the creation of thematic teaching materials tailored for Class III students, revolutionizing environmental education through interactive and immersive learning experiences. Additionally By integrating cutting-edge pedagogical approaches with the importance of environmental conservation, this research uncovers a transformative framework for encouraging ecological awareness among young students.